Transport the Injured People to Hospitals on the Post-Disasters - Babaqi, Tareq Abdulrahman Mohammed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The objective of thesis is to propose better design of EMU Library by assessing its furniture and its impact on the understudy stance, execution and consideration. We discovered that the EMU library furniture (Chairs and Tables) are not suitable for students' health. One hundred and fifty seven undergraduate and postgraduate were used as a subject. They were between 16 to 45 years old. Twelve measurements of anthropometry of the students were measured including: Shoulder Height (SDH), Stature, Shoulder Elbow Height, Popliteal Height, Knee Height, Forearm Length, Buttock-to-Popliteal Length, Elbow Sitting Height(EH), Hip Width, Sitting Height, Sitting, Overhead Stretch Height, and Eye Height. Standard deviation, mean, percentiles, least and greatest estimation of measurements were figured. Arrangement of the present light of the library was assessed by recording the illumination level on every table on second floor of library. The present light system was found to neglect to consent to ergonomic configuration criteria. Another configuration of furniture and recommendation of light system proposed to enhance the level of solace for students. Keywords: Ergonomic design criteria, Anthropometric data, Mismatch, Percentile

ÖZ: Bu çalışmanın amacı, DAÜ Kütüphanesi mobilya ve öğrenci duruş, performans ve dikkat üzerindeki etkisini değerlendirmek. Yüz elli yedi öğrenci denek olarak kullanıldı. Yaşları 16 ile 45 yıl arasında değişmektedir. konuların Oniki antropometrik veriler de dahil olmak üzere önlemler vardı: boyu, Omuz Yüksekliği, Omuz Dirsek yüksekliği, Kalça-Popliteal uzunluğu, Popliteal yüksekliği, Diz Yüksekliği, Önkol Uzunluğu, Kalça genişliği, Dirsek oturma Yüksekliği, Oturma Yüksekliği, Oturma Göz Yüksekliği ve Tepegöz streç yüksekliği. ortalama, standart sapma, yüzdelik, minimum ve antropometrik boyutlar maksimum değeri hesaplandı. Kütüphanenin mevcut ışık sistemi kütüphanenin ikinci katta her masada aydınlatma seviyesini gözlemleyerek değerlendirildi. Geçerli ışık sistemi ergonomik tasarım kriterlerine uymayan bulunmuştur. mobilya ve ışık sistemi önerisi yeni bir tasarım öğrencilerin için konfor düzeyini artırmak için önerildi. Anahtar Kelimeler: Ergonomi tasarım kriterleri, Antropometrik veriler, Uyuşmazlığı, Yüzdelik
Doctor of Philosophy in Industrial Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2021. Supervisor: Prof. Dr. Bela Vizvari.
Keywords: Industrial Engineering; Disaster Management--Transporting--Injured People to Hospitals; Disaster Technology--Management; Humanitarian logistics; Post-disaster; Voronoi diagram; Partial oracle; Scheduling problems